2023
DOI: 10.1161/jaha.122.028200
|View full text |Cite
|
Sign up to set email alerts
|

Association of Joint Genetic and Social Environmental Risks With Incident Myocardial Infarction: Results From the Health and Retirement Study

Abstract: Background Myocardial infarction (MI) is a significant clinical and public health problem worldwide. However, little research has assessed the interplay between genetic susceptibility and social environment in the development of MI. Methods and Results Data were from the HRS (Health and Retirement Study). The polygenic risk score and polysocial score for MI were classified as low, intermediate, and high. Using Cox regression models, we assessed the race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These results highlight the importance of jointly modeling SDOH and PRS when estimating CHD risk. Our approach extends previous efforts to create SDOH scores for CVD (25,26) and is likely applicable to other common diseases. For example, a recent study showed that T2D prevalence and BMI were influenced by PRS and SDOH in the US and the UK (27).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These results highlight the importance of jointly modeling SDOH and PRS when estimating CHD risk. Our approach extends previous efforts to create SDOH scores for CVD (25,26) and is likely applicable to other common diseases. For example, a recent study showed that T2D prevalence and BMI were influenced by PRS and SDOH in the US and the UK (27).…”
Section: Discussionmentioning
confidence: 85%
“…These results highlight the importance of jointly modeling SDOH and PRS when estimating CHD risk. Our approach extends previous efforts to create SDOH scores for CVD (25,26) and is likely applicable to other common For example, a recent study showed that prevalence and BMI were influenced by PRS and SDOH in the US and the UK (27). However, since SDOH CHD was specifically developed for CHD, it is different from other commonly used social and economic deprivation indices based on area-level socioeconomic measures.…”
Section: Discussionmentioning
confidence: 93%
“…For physical activity, we calculated a total weekly metabolic equivalent time period for four activities: walking for pleasure, heavy DIY, strenuous sports and other exercises. 28 We classified participants into three tertiles according to the total weekly metabolic equivalent time period, and considered the top layer as adequate physical activity, 19 and the other layers as an unhealthy level. We measured dietary quality using a dietary recommendation for cardiovascular diseases.…”
Section: Methodsmentioning
confidence: 99%
“…Higher polygenic scores represent more depressive symptoms or better subjective well-being. Following the approach in the previous studies 55,56 , the polygenic scores were categorized into low (quintile 1 for depressive symptoms and quintile 5 for subjective well-being), intermediate (quintiles 2-4), and high (quintile 5 for depressive symptoms and quintile 1 for subjective well-being) genetic risk.…”
Section: Country-level Factorsmentioning
confidence: 99%